Green nanomaterials : from bioinspired synthesis to sustainable manufacturing of inorganic nanomaterials /: from bioinspired synthesis to sustainable manufacturing of inorganic nanomaterials. ([2020]) - Patwardhan, Siddharth V; Staniland, Sarah S
No abstract available